Hesse : the wanderer and his shadow - Decker, Gunnar, 1965- (Harvard University Press, 2018)
Hermann Hesse's stories inspired nonconformity and a yearning for universal values to supplant the political fanaticism tearing Europe apart. Initially, critics thought his work inaccessible to Americans, but the counterculture of the 1960s--and subsequent generations of admirers--emphatically proved the opposite. Gunnar Decker weaves together previously unavailable sources to offer a unique interpretation of the life and work of Hermann Hesse. Drawing on newly discovered correspondence between Hesse and his psychoanalyst Josef Lang, Decker shows how Hesse reversed the traditional roles of therapist and client, and rethinks the relationship between Hesse's novels and Jungian psychoanalysis. Readers who can now explore Hesse's correspondence with Thomas Mann and Stefan Zweig--the latter recently unearthed--will come away with a better understanding of the author's profound sense of alienation from his contemporaries.--